Daily zero-reporting for suspect Ebola using short message service (SMS) in Guinea-Bissau. (September 2016) - Cáceres, V.M.; Cardoso, P.; Sidibe, S.; Lambert, S.; Lopez, A.; Pedalino, B.; Herrera Guibert, D.J.
Abstract: Objective: Intensified surveillance will be vital in the elimination phase to verify Ebola-free status and mitigate potential reemergence of the disease in West Africa. Zero-reporting from high-risk districts is a key strategy for surveillance. Our objective was to implement a pilot investigation to assess the feasibility of using short message service (SMS) texting for daily reporting of Ebola cases under investigation (CUI) in Guinea-Bissau in the context of an ongoing emergency-response training program known as Surveillance Training for Ebola Preparedness (STEP). Study design: Prospective cohort (pilot investigation) Methods: The reporting period for the SMS pilot was January 24–March 24, 2015. STEP was conducted for two sequential groups during January 19–March 27, 2015 in Bissau, Guinea-Bissau. Training on SMS daily reporting occurred over one hour during the first week of didactic training of each group. Fourteen participants (nine from the first group and five from the second), including one surveillance officer from each of the 13 regions in Guinea-Bissau and one from the national laboratory, were selected as reporters, receiving a simple cell phone for sending SMS indicating the number of CUI for Ebola. The WHO suspect Ebola case definition was used initially and then modified on day 32 of the pilot. The text message was sent to the WiFi-connected smartphone at the Instituto Nacional Saúde Pública (INASA). The smartphone utilised an SMS-gateway application (Ushahidi SMSsync Android App) to upload the data to the Magpi cloud application. Results: The average daily reporting from the first group was 7.7 of 9 (86%) and for the second group was 4.1 of 5 (82%). For the two groups combined, the reporting rate was 85%. Among the 14 reporters the median reporting rate was 85% (range 36%–100%). No cases meeting the definition for an Ebola CUI were reported during the 60 days. Conclusions: Real-time, SMS-based, daily zero-reporting can be implemented in a rapid, simple way in a low resource country. We believe that the high compliance rates were due to the simplicity and familiarity of SMS and heightened sensitivity that resulted from STEP to the importance of zero-reporting in the midst of an Ebola epidemic in neighbouring countries. This model could be useful for rapid scale-up and implementation of alert systems in other outbreaks and public health emergencies. Highlights: As of September 2015, the Ebola outbreak in West Africa has claimed over 10, 000 lives. Zero-reporting is a key surveillance strategy for disease elimination. Real-time, SMS-based, daily zero-reporting can be implemented in a rapid, simple way in a low resource country. The real-time, zero-reporting through SMS model could be useful for rapid scale-up and implementation of alert systems in other outbreaks and public health emergencies.